Apakah Orang Tua Menggunakan Internet dan Media Sosial dalam Pencarian Informasi Kesehatan Anak? - Riza Hayati Ifroh; Lies Permana (Jurnal Kesehatan Komunitas, 2022)
Parents in the digital era increasingly use the internet and social media to search for health information on their children, as well as provide opportunities to interact with other users to discuss children's health issues. The purposes of this study is to analyze the patterns of internet use and social media use by parents based on the age category of the child and the most of platform and health topic information that access by parents. The design study was a cross-sectional quantitative study. The target group research was parents who have children aged < 5 to 12 years, have internet access, actively use gadgets, and agreed to be a participant in this study. The technique of sampling used nonprobability sampling with accidental sampling. The data was taken by Google form application to 285 respondents. The results of this study were most of the parents were in urban areas (65.3%) with the majority being housewives (79.6%). The use of the internet by parents to search for health information with a frequency of less than 2 times per week (47.4%) uses a smartphone (91.9%). There is a statistical difference in the use of Instagram social media for parents in searching for health and non-health information (p-value: <0.001), and the use of Tiktok for non-health information (p-value: <0.001). The topics that are most reviewed by parents with children under the age of 5 are allergies, child nutrition, and the dangers of using gadgets in children (screen time). Parents who have children aged 5-11 years and 12 years and over are also looking for information about child nutrition, screen time, and extras such as accidents, bullying, and reproductive health.